The peculiarities of processing of constructional materials by pulse plasma streams - Zhukeshov, A. M.; Gabdullina, A. T.; Pak, S. P.; Amrenova, A. U. (Recent Contributions to Physics, 2013)
In this paper presented the results of studies of stainless steel samples surface after modification by pulsed plasma flows, processing by single and multiple time. The modification carried out on CPU-30 pulsed plasma accelerator worked at continuously filling mode. The working gas air on pressure 0.04-0,5 mmHg and energy density of plasma 0-40 J/cm2 . The changes of properties of materials investigated by SEM and XRD methods. The evolution of the grain, as a structural component of steel, depending on the basic processing parameters,was researched. Is shown, that changes in the structure of the steel influence of the microhardness of material surface. The peculiarities of influence of powerful plasma impact on constructional materials is the the formation of hardening nitride and carbide phases.